ANALISA SISTEM SUPLAI AIR PRODUKSI DAN AIR PENDINGIN UNTUK KEHANDALAN OPERASI DI PLTU PULANG PISAU (2X66MW) - Hendra Hadi Saputra; Rudi Siswanto (Scientific Journal of Mechanical Engineering Kinematika, 2019)
This study aims to determine the water supply / discharge system of water pretreatment station equipment which is then processed for the purpose of operating a steam power plant. In the distribution process, the reliability of the equipment and the resulting discharge will be observed whether it is in accordance with the provisions for the ideal operation or not. The expected discharge is 518 m3 / h according to the water balance so that the plant can operate full load (2x66 MW). With this condition, the company is expected to benefit. In the actual conditions this ideal discharge condition is not achieved so that the impact of the plant cannot operate full load (2x66 MW). With water conditions that do not match these expectations, it is feared that the company will continue to suffer losses. In fact, this study only obtained a maximum discharge of 402.2 m3 / h. From this figure there is a difference in water debit of 115.8 m3 / h. Furthermore, this debit shortage must be overcome so that the generator can meet the maximum full load performance. For long-term steps, standby backup equipment must be provided in anticipation of the operation.